Interpersonal Relations Within the Context of Resource Groups for People With Severe Mental Illness: A Narrative Approach - Tjaden, Cathelijn D.; Boumans, Jenny; Mulder, Cornelis L.; Kroon, Hans (Frontiers in Psychiatry, 2021)
Objective. The resource group method intends to promote patients’ agency and self-management and to organize meaningful partnerships between patients and their informal and formal support systems. The aim of this study was to enhance the understanding of interpersonal dynamics that arise within resource groups for people with severe mental illness. Insight into these unfolding processes would enable improved implementation of the resource group method so that it contributes to establishing a positive social environment, which can lead to more enduring recovery. Methods. We performed a narrative analysis of transcripts and field notes obtained in a longitudinal, qualitative study on the resource group method. The stories of four different resource groups were reconstructed and analyzed in depth. Data included a total of 36 interviews (with patients, significant others, and mental health professionals) and 18 observations of resource group meetings. Results. The degree to which the resource group method actually contributes to recovery was based on the extent to which the existing roles of and patterns between the patient and his/her resource group members were altered. Breaking through old patterns of inequality and the joint search for a new balance in relationships proved to be crucial processes for establishing an empowering resource group. The four cases showed that it takes time, patience, and small steps back and forth to overcome the struggles and fears related to finding new ways of relating to each other. An honest and reflective atmosphere in which all participants are encouraged to participate and be curious about themselves and each other is essential for changes in interpersonal dynamics to emerge. Such changes pave the way for individuals with SMI to find their own voices and pursue their unique recovery journeys. Conclusions. The functioning of the resource group and the ability of the involved members to respond in new ways are important when working toward the patient’s recovery goals. The resource group method should therefore not be considered an intervention to organize informal support for the patient, but a platform to expose and adjust the functioning of the patient’s social network as a whole.